First Description of Scrotal Testicles in a Dog Affected by 78, XX Testicular Disorder of Sex Development. Issue 5 (16th August 2014) - Del Carro, AP; Rosset, E; Josson‐Schramme, A; Lambert, V; Buff, S
Contents An eight‐month‐old female dog presented with ambiguous external genitalia. A thorough clinical examination together with various imaging techniques and a histology examination showed the presence of two testicles linked to both the Mullerian and Wolffian ducts. The discovery of the 78, XX SRY‐negative karyotype led to the diagnosis of incoherence between the chromosomal and gonadal sex, which is typical for a 78, XX testicular disorder of sex development. Our case was unique because the testicles were still located in their normal scrotal position, whereas the literature contains reports of the presence of cryptorchid testicles in this karyotype setting. To our knowledge, this is the first case that describes an SRY‐negative 78, XX testicular disorder of sex development with bilateral scrotal testicles.